ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT BERWIRAUSAHA MAHASISWA - Taruli Fransiska Lumbantoruan (Pendidikan Ekonomi, 2010)
This study aims to examine the individual internal and external factors of entrepreneurial interest. Data were obtained from questionnaires. Respondents in this study were students Economics Department of Education Unesa in the academic year  of 2005. The data were then analyzed by using factor analysis. The results indicate that students interest in entrepreneurship is influenced by four factors, which is obtained by reducing the 21 variables. Reduced variables include business skills, cooperative skills, optimism and committment, financial, social, service, business experience, motive of achievement, management skill in business, taking advantages of personal skills, creativity and innovativeness, high morale, future-orientation, not getting quickly satisfied, high discipline, always looking for opportunities, independence, ability to regulate emotions, not getting easily discouraged, formal education, teacher educators.